Preparation of Cu3SbSe4 Doping with Aluminum and Studying on its Thermoelectrical Properties (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The electrical transport and thermoelectric properties of Cu3Sb1-xAlxSe4 (x = 0, 0.03, 0.05 &0.07) compounds are investigated in the temperature range of (298 – 553) K. The results indicate that with increasing Al content from ( x = 0) to (x =0.07), hole concentration increases monotonically from (2.03×1018 to 2.82 × 1018 cm-3) due to the substitution of Al3+ for Sb5+, thus leading to a large decrease in the electrical resistivity of Cu3Sb1-xAlxSe4. Meanwhile, the increase in hole concentration leads to a transition from a non-degenerate (x = 0) to a partial degenerate (x = 0.05, 0.07) and then to a degenerate state   (x = 0.07). The power factor (PF) of all the Al-doped Cu3Sb1-xAlxSe4 samples is remarkably improved due to the optimization of hole concentration. Lattice thermal conductivity kL of the heavily doped sample(x = 0.07) is reduced. As a result, a large thermoelectric figure of merit ZT = 1.28 is obtained for Cu3Sb0.97Al0.03Se4 at 458K, which is around 5 times as large as that of the un-doped Cu3SbSe4 sample.